ON THE DEVELOPMENT OF LOCAL GOVERNMENT ORGANIZATIONS - พระณัฐพงษ์ ญาณเมธี (ไกรเทพ); ทิพพ์ประจง, มะลิ (Journal of MCU Phetchaburi Review, 2021)
Problems and challenges of Thailand in the framework of the National Development and Reform Strategy are related to the mission of the Department of Local Administration, to strengthen the democratic regime of government with the King as the Head of State To be stable Sustainability and local strengthening According to the form of government in the Democracy in the area to be continuously strengthened As a completely democratic local government Along with giving importance to With promoting and developing youth readiness residents Democracy of local government organizations Let the local government organization be a learning center for Democracy for the people. To contribute to the development of Democracy in which the local people and the broader society, both locally and internationally, are recognized in the local Democracy of Thailand. Building local self-sufficiency capacity and being an essential spatial mechanism for guiding the development of the area and improving the quality of life of the people; emphasizes linking the sufficiency economy philosophy to the development of administration and the provision of public services according to the local mission context. And the most important thing is to preserve the knowledge of the philosophy of sufficiency economy and the working way of promoting local government in Thailand. Driving the community for the community by allowing people to be able to select their representatives to be leaders in community development for change and to be able to represent the people in driving the community development plan according to the constitutional law. Established channels for people in each area to make appropriate decisions in selecting an importer to represent themselves.